Polymorphisms and Interspecies Differences of the Activating and Inhibitory FcγRII of Macaca nemestrina Influence the Binding of Human IgG Subclasses() - Trist, Halina M. (2013)
Little is known of the impact of Fc receptor polymorphism in macaques on the binding of human IgG (huIgG) and nothing is known of this interaction in the pigtail macaque (M. nemestrina) which is used in preclinical evaluation of vaccines and therapeutic antibodies. We defined the sequence and huIgG binding characteristics of the M. nemestrina activating FcγRIIa (mnFcγRIIa) and inhibitory FcγRIIb (mnFcγRIIb) and predicted their structures using the huIgGFc:huFcγRIIa crystal structure. Large differences were observed in the binding of huIgG by mnFcγRIIa and mnFcγRIIb compared to their human FcR counterparts. MnFcγRIIa has markedly impaired binding of huIgG1 and huIgG2 immune complexes compared to huFcγRIIa (His131). In contrast, mnFcγRIIb has enhanced binding of huIgG1 and broader specificity as, unlike huFcγRIIb, it avidly binds IgG2. Mutagenesis and molecular modelling of mnFcγRIIa showed that Pro159 and Tyr160 impair the critical FG loop interaction with huIgG. The enhanced binding of huIgG1 and huIgG2 by mnFcγRIIb was shown to be dependent on His131 and Met132. Significantly, both His131 and Met132 are conserved across FcγRIIb of rhesus and cynomolgus macaques. We identified functionally significant polymorphism of mnFcγRIIa, wherein Pro at position 131, also an important polymorphic site in huFcγRIIa, almost abolished binding of huIgG2 and huIgG1 and reduced binding of huIgG3 compared to mnFcγRIIa His131. These marked interspecies differences in IgG-binding between human and macaque FcRs and polymorphisms within species have implications for pre-clinical evaluation of antibodies and vaccines in macaques.